Organizing Social Protection in Federal States : International Examples of Federalism and Social Protection and Implications for Pakistan - Matsuda, Yasuhiko (World Bank, Washington, DC, 2018)
Pakistan’s social protection system is still in a nascent stage of development and so is the country’s fiscal and institutional architecture for inter-governmental relations. In particular, the implicit devolution of social protection and related functions in the eighteenth constitutional amendment in 2010 has created a level of uncertainty and certain lack of consensus about the definitive roles of federal versus provincial governments in providing social protection to the population. This note is intended to contribute to informed debates about the future of federalism and social protection in Pakistan. It describes key features of the ways in which mature federations have organized their social protection sector and summarizes possible implications for Pakistan. Drawing on the descriptions on how social protection functions are distributed across levels of government in ten relatively mature federations (including South Africa which is constitutionally a unitary state but is highly decentralized in expenditure assignment), this discussion note is intended as merely one type of input for policy-makers in Pakistan to consider how best to organize the social protection functions across levels of government in the country’s evolving inter-governmental relations.